Alaskan Inuit Food Security Conceptual Framework: How to assess the Arctic from an Inuit Perspective. - Unkn Unknown (Inuit Circumpolar Council, 2015)
Drastic changes are occurring within our world. We are on the forefront of these changes. We have lived here for millennia and have grown and changed with all that is around us. All that is around us physically and spiritually nourishes us, and our culture reflects the Arctic because we are part of this ecosystem. With these rapid changes comes the need for holistic information based on Indigenous Knowledge (IK) and science. With this understanding, we brought our concerns regarding the impact of Arctic changes on our food security to forums throughout the Arctic. Through these conversations, it quickly became evident that we were referring to something different than those we were holding the discussions with. We have often heard people within academia, policy and management speak to us of nutritional value, calories and money needed to purchase food. All of this is important, but not what we are talking about when we say food security. We are speaking about the entire Arctic ecosystem and the relationships between all components within. We are talking about how our language teaches us when, where and how to obtain, process, store and consume food; the importance of dancing and potlucks to share foods and how our economic system is tied to this. We are talking about our rights to govern how we obtain, process, store and consume food; about our IK and how it will aid in illuminating the changes that are occurring. We are talking about what food security means to us, to our people, to our environment and how we see this environment. We are talking about our culture. From the realization that we need to fully share what our food security means within the Alaska Arctic, this project was born. There has been a lot of positive work completed and work that is ongoing to increase academic and governmental understanding of food security. The outcomes of this project come directly from us, Alaskan Inuit, to share what our food security is, how to assess changes occurring and how to move forward in a way that will strengthen our food security. The objectives for the project were clear from the beginning – define food security, identify what the drivers (or causes) of food (in)security are, create a conceptual framework and provide an assessment process to determine Alaskan Inuit food security. What resulted is something much more. As we came together through community meetings, oneon- one and group interviews, regional workshops and numerous conversations, we realized that the drivers of our food security are all the same and that what make up food security within each of our identities, villages and regions is the same.